Intradermal Vaccination With Adjuvanted Ebola Virus Soluble Glycoprotein Subunit Vaccine by Microneedle Patches Protects Mice Against Lethal Ebola Virus Challenge. (8th June 2018) - Liu, Ying; Ye, Ling; Lin, Fang; Gomaa, Yasmine; Flyer, David; Carrion, Ricardo; Patterson, Jean L; Prausnitz, Mark R; Smith, Gale; Glenn, Gregory; Wu, Hua; Compans, Richard W; et al.
Abstract: In this study, we investigated immune responses induced by purified Ebola virus (EBOV) soluble glycoprotein (sGP) subunit vaccines via intradermal immunization with microneedle (MN) patches in comparison with intramuscular (IM) injection in mice. Our results showed that MN delivery of EBOV sGP was superior to IM injection in eliciting higher levels and longer lasting antibody responses against EBOV sGP and GP antigens. Moreover, sGP-specific immune responses induced by MN or IM immunizations were effectively augmented by formulating sGP with a saponin-based adjuvant, and they were shown to confer complete protection of mice against lethal mouse-adapted EBOV (MA-EBOV) challenge. In comparison, mice that received sGP without adjuvant by MN or IM immunizations succumbed to lethal MA-EBOV challenge. These results show that immunization with EBOV sGP subunit vaccines with adjuvant by MN patches, which have been shown to provide improved safety and thermal stability, is a promising approach to protect against EBOV infection.